Pengaruh Ukuran KAP, Ukuran Perusahaan dan Manajemen Laba terhadap Integritas Laporan Keuangan - Intan Paulina Lubis; Lailah Fujianti; Rafrini Amyulianthy (Ultima Accounting : Jurnal Ilmu Akuntansi, 2018)
This study aims to analyze the effect of KAP size, firm size and earnings management on the integrity of financial statements. The integrity of financial statements is the extent to which the financial statements presented indicate true and honest information. This study was taken because there are still contradictions from previous studies. This study uses secondary data. The population in this study is the consumer goods industry companies listed on the Indonesia Stock Exchange in 2012-2016. Determination of the sample by purposive sampling method, there are 13 samples from the total population of 40. The method used to analyze the data is panel data regression analysis, Eviews 9. Regression analysis results show that firm size negatively significant to the integrity of financial statements. While the size of KAP and earnings management have no significant effect on the integrity of financial statements.Keywords: Financial Statement Integrity, Company Size, Company Size and Earnings Management